Sustaining non-profit organizations: Strategic, managerial and financial perspectives - Yara Harb; Lara Khabbaz; Marwan Azouri; Sandra Estephan (PLoS ONE, 2026)
Purpose This study explores the complex challenges that Non-Governmental Organizations (NGOs) face. The research highlights the impact of strategic planning, managerial capabilities and financial management on NGOs sustainability. Sustainability is defined to mean durability and continuity of the organization. Design/methodology/approach Data were collected from 75 NGOs using a survey to examine the roles of strategic planning, financial management, and managerial skills in supporting NGO sustainability. Findings Contrary to initial assumptions, the findings reveal that while strategic planning and strong managerial capabilities are crucial for long-term sustainability, financial management does not show a direct impact. The study suggests that NGOs should focus on developing comprehensive strategic plans and enhancing their managerial capacities to effectively navigate complex environments and achieve their goals. Originality This research contributes to the conversation on NGO management by highlighting the important intersection of resource-based competencies and stakeholder engagement in building resilient and successful organizations.